2023
DOI: 10.1021/acsnano.2c12793
|View full text |Cite
|
Sign up to set email alerts
|

Water-Soluble Chemically Precise Fluorinated Molecular Clusters for Interference-Free Multiplex 19F MRI in Living Mice

Abstract: Fluorine-19 magnetic resonance imaging (19F MRI) is gaining widespread interest from the fields of biomolecule detection, cell tracking, and diagnosis, benefiting from its negligible background, deep tissue penetration, and multispectral capacity. However, a wide range of 19F MRI probes are in great demand for the development of multispectral 19F MRI due to the limited number of high-performance 19F MRI probes. Herein, we report a type of water-soluble molecular 19F MRI nanoprobe by conjugating fluorine-contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 69 publications
0
15
0
Order By: Relevance
“…in a single-site or multi-site manner. 375 They can function as a single-molecular nanoplatform or assemble into nanoparticles of relatively large size for drug delivery, fluorescent imaging, tissue engineering, and therapeutic applications. [376][377][378][379] For instance, an organic-inorganic hybrid POSS-porphyrin photosensitizer was synthesized by conjugating porphyrin-N 3 to (vinyl) 7 -POSS-alkyne via copper-catalyzed click chemistry.…”
Section: Synthesis It Is Well Known That the Sto ¨Ber Methods Was Fir...mentioning
confidence: 99%
“…in a single-site or multi-site manner. 375 They can function as a single-molecular nanoplatform or assemble into nanoparticles of relatively large size for drug delivery, fluorescent imaging, tissue engineering, and therapeutic applications. [376][377][378][379] For instance, an organic-inorganic hybrid POSS-porphyrin photosensitizer was synthesized by conjugating porphyrin-N 3 to (vinyl) 7 -POSS-alkyne via copper-catalyzed click chemistry.…”
Section: Synthesis It Is Well Known That the Sto ¨Ber Methods Was Fir...mentioning
confidence: 99%
“…Among other nuclei suitable for MRI, 19 F draws the attention of the research community because of its high MR sensitivity (comparable to that of 1 H), 100 % natural abundance, and negligible biological background [24–31] . Besides, the wide range of 19 F chemical shifts (>350 ppm) and the diversity of biocompatible fluorine‐containing agents permit multi‐spectral color‐coded 19 F MRI that is capable of tracing multiple targets [32–36] . In addition, in vivo quantitative analysis, which is difficult for many imaging techniques, is enabled by the quantitative nature of MR and the low biological background of 19 F [37–38] .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, exploring facile strategies to fabricate highperformance 19 F MRI CAs with acceptable preparation procedures still requires attention and effort. Some research has revealed that to achieve high-resolution in vivo 19 F MRI, a very high concentration of 19 F MRI CAs (above 50 mM) is normally administrated, [47][48][49] which indicates that prolonging the circulation time of the 19 F MRI CAs in vessels in vivo and promoting their accumulation inside the imaging lesion in vivo are pivotal as well. Thus, fabricating high-performance 19 F MRI CAs with a long T 2 relaxation time and long circulation time in vivo and with excellent biocompatibility by a simple, efficient, and economical strategy demands increasing attention from researchers.…”
Section: Introductionmentioning
confidence: 99%